Inter-session test-retest reliability of the quantified y balance test - Johnston, W.; O`Reilly, M.; Coughlan, G.; Caulfield, B. (Proceedings of the 6th International Conference on Sport Sciences Research and Technology Support - Volume 1: icSPORTS, 2018)
The Y Balance test is the most common dynamic balance assessment used in clinical practice and research. However, the traditional measure of performance, the reach distance, fails to provide detailed information pertaining to the control of balance during the reach task. Recent research has demonstrated that a single wearable inertial sensor can capture detailed information pertaining to balance performance during the Y balance test, not captured by the traditional reach distances. To date, no research has been conducted investigating the inter-session test-retest reliability of the inertial sensor instrumented YBT. Thirty -two young healthy adults, aged between 18-40 were recruited as part of this study. Participants completed the quantified YBT protocol during two testing sessions, separated by 7-10 days. The findings from this study demonstrated that 26/36 (anterior), 31/36 (posteromedial) and 33/36 (posterolateral) quantified variables demonstrated good-excellent intra-session te st-retest reliability. These findings suggest that the inertial sensor quantified YBT can provide a reliable measure of dynamic balance performance. Further research is required to investigate the capability of the quantified YBT to identify individuals at risk of injury/ disease and track recovery/ response to intervention.